The piriform, perirhinal, and entorhinal cortex in seizure generation - Vismer, Marta S.; Forcelli, Patrick A.; Skopin, Mark D.; Gale, Karen; Koubeissi, Mohamad Z. (Frontiers in Neural Circuits, 2015)
Understanding neural network behavior is essential to shed light on epileptogenesis and seizure propagation. The interconnectivity and plasticity of the limbic and cortical regions of the mammalian brain provide the substrate for the hypersynchrony and hyperexcitability associated with epilepsy and seizure activity. Recurrent unprovoked seizures are the hallmark of epilepsy, and limbic epilepsy is the most common type of medically-intractable focal epilepsy in adolescents and adults that necessitates surgical evaluation. In this review, we describe the role and relationships among the piriform (PIRC), perirhinal (PRC), and entorhinal cortex (ERC) in seizure-generation and epilepsy. The inherent function, anatomy, and histological composition of these cortical regions are discussed. In addition, the neurotransmitters, intrinsic and extrinsic connections, and the interaction of these regions are described. Furthermore, we provide evidence based on clinical research and animal models that suggest that these cortical regions may act as key seizure-trigger zones and, even, epileptogenesis.